Exit Problems for Jump Processes Having Double-Sided Jumps with Rational Laplace Transforms - Yuzhen Wen; Chuancun Yin (Abstract and Applied Analysis)
We consider the two-sided first-exit problem for a jump process having jumps with rational Laplace transform. We derive the joint distribution of the first passage time to two-sided barriers and the value of process at the first passage time. As applications, we present explicit expressions of the dividend formulae for barrier strategy and threshold strategy.